1996
DOI: 10.1021/ma950930g
|View full text |Cite
|
Sign up to set email alerts
|

Isospecific Oligo-/Polymerization of Styrene with Soluble Cationic Nickel Complexes. The Influence of Phosphorus(III) Ligands

Abstract: The influence of several phosphorus(III) ligands upon the activity and the stereoregulation ability of the soluble organometallic complex [Ni(η3-(2-methylallyl))(η4-COD)]PF6 (COD = 1,5-cyclooctadiene), 1, is studied. There is a general increase of the catalytic activity which can be associated with the P(III) ligand's lability. A detailed analysis of the mass distribution and microstructure is carried out by GPC and 1H and 13C NMR of the solvent-fractionated polymers. In the majority of cases, regioregular low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…The 13 C NMR spectra indicated that the obtained polymers were isotactic-rich atactic. [22] The MALDI-TOF mass spectra of the polymer produced with complex 2 featured peaks corresponding to the molecular formula [(C 8 H 8 ) n Ag]…”
Section: Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C NMR spectra indicated that the obtained polymers were isotactic-rich atactic. [22] The MALDI-TOF mass spectra of the polymer produced with complex 2 featured peaks corresponding to the molecular formula [(C 8 H 8 ) n Ag]…”
Section: Polymerizationmentioning
confidence: 99%
“…These observations are in agreement with a cationic mechanism for styrene polymerization, [2,23] although a coordination/insertion mechanism involving an Ni-H species cannot be ruled out. [22,24] Selected complexes were also tested in the polymerization of phenylacetylene in the presence of an excess of MAO (Table 2). Moderate activities (TONs up to 600) were obtained under conditions similar to those for styrene.…”
Section: Polymerizationmentioning
confidence: 99%
“…13 C NMR spectra of polymers were carried out on a Bruker AC 500 spectrometer instrument at room temperature in CDCl 3 solution using TMS as internal standard. Oligomer analyses were performed by GC/MS on a Hewlett Packard GC6890/MS5973 equipment.…”
Section: Measurementsmentioning
confidence: 99%
“…According to the result reported by Ziegler et al [35] , there is a residual hydroxyindanone-iminate ligand on the active species which may influence catalytic performance by electronic and steric effects (Scheme 1). The analyses on the 13 C NMR spectra of polystyrene end-groups can help further to elucidate the polymerization mechanism (Figure 2) [11][12][13][24][25][26]34] .…”
Section: Run Complexmentioning
confidence: 99%
See 1 more Smart Citation